Researching Belief without Asking Religious Questions - Day, Abby (Fieldwork in religion, 2009)
A unique research method was designed to answer the question "What do people believe in nowadays and how do we find out?" This approach was intended to research belief by asking non-religious questions of apparently non-religious people. The qualitative method, detailed here, produced data that led me to conclude that statements of religious affiliation are often expres-sions of "believing in belonging," where people associate with religion to reinforce ethnic, familial or other social identities. Fieldwork issues such as informant selection, interviews and data interpretation are discussed in detail.